Intelligent data engineering and automated learning -- IDEAL 2016 : 17th International Conference, Yangzhou, China, October 12-14, 2016, Proceedings /: 17th International Conference, Yangzhou, China, October 12-14, 2016, Proceedings. (2016) - Unknown
No abstract available